Variation in SWI/SNF Chromatin Remodeling Complex Proteins is Associated with Alcohol Dependence and Antisocial Behavior in Human Populations. (27th October 2017) - Mathies, Laura D.; Aliev, Fazil; ,; Davies, Andrew G.; Dick, Danielle M.; Bettinger, Jill C.
Abstract : Background: Testing for direct gene or single nucleotide polymorphism replication of association across studies may not capture the true importance of a candidate locus; rather, we suggest that relevant replication across studies may be found at the level of a biological process. We previously observed that variation in 2 members of the switching defective/sucrose nonfermenting (SWI/SNF) chromatin remodeling complex is associated with alcohol dependence (AD) in the Irish Affected Sib Pair Study for Alcohol Dependence. Here, we tested for association with alcohol‐related outcomes using a set of genes functioning in the SWI/SNF complex in 2 independent samples. Methods: We used a set‐based analysis to examine the 29 genes of the SWI/SNF complex for evidence of association with (i) AD in the adult Collaborative Study on the Genetics of Alcoholism (COGA) case‐control sample and (ii) antisocial behavior, hypothesized to be a genetically related developmental precursor, in a younger population sample (Spit for Science [S4S]). Results: We found evidence for association of the SWI/SNF complex with AD in COGA ( p  =   0.0435) and more general antisocial behavior in S4S ( p  =   0.00026). The genes that contributed most strongly to the signal in COGA were SS18L1, SMARCD1, BRD7, BCL7B, SMARCB1, and BCL11A . In the S4S sample, ACTB, ARID2, BCL11A, BCL11B, BCL7B, BCL7C, DPF2, and DPF3 all contributed strongly to the signal. Conclusions: We detected associations between the SWI/SNF complex and AD in an adult population selected from treatment‐seeking probands and antisocial behavior in an adolescent population sample. This provides strong support for a role for SWI/SNF in the development of alcohol‐related problems. Abstract : Replication of genetic association at the level of the biological process, rather than the gene, may reveal important mechanisms underlying alcohol dependence (AD). We used a set of all genes encoding members of the SWI/SNF chromatin remodeling complex to test for association with AD in COGA and antisocial behavior in Spit for Science (S4S) and found association with AD (yellow), antisocial behavior (blue), and both (green). These associations suggest a role for the regulation of chromatin structure in alcohol‐related outcomes.